1994
DOI: 10.3382/ps.0730610
|View full text |Cite
|
Sign up to set email alerts
|

Feed and Water Consumption, Growth, and Mortality of Male Broilers

Abstract: Daily feed use, water use, body weight, and mortality of Cobb x Cobb male broilers over 8-wk growout periods were measured for 10 consecutive growouts in four commercial-scale broiler houses (121.0 x 12.1 m each). Polynomial equations were developed to relate bird age to body weight, daily feed and water use, cumulative weekly feed and water use, and cumulative mortality. Weekly feed conversion was derived from growth and feed use data and was depicted by a third-order polynomial equation. Dead bird weight was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

1994
1994
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(16 citation statements)
references
References 4 publications
0
16
0
Order By: Relevance
“…Bird performance and litter management practice between growouts for the 16 growouts are listed in table 2. Because bird performance was similar in all houses for each growout (Xin et al, 1994), farm averages are reported here. As indicated in table 2, growouts raised on old litter tended to coincide with higher condemnation than those grown on new bedding.…”
Section: Resultsmentioning
confidence: 99%
“…Bird performance and litter management practice between growouts for the 16 growouts are listed in table 2. Because bird performance was similar in all houses for each growout (Xin et al, 1994), farm averages are reported here. As indicated in table 2, growouts raised on old litter tended to coincide with higher condemnation than those grown on new bedding.…”
Section: Resultsmentioning
confidence: 99%
“…overall mortality, first week mortality and mortality after seven days. This classification was used because previous research about mortality rate in average broiler production was shown to follow typical patterns with a peak in mortality at day three and four after placement, a stable low mortality rate during the rest of the production cycle with a slight increased mortality rate during the sixth week of broiler production [14,15,16,17]. For this reason a distinction was made between mortality rate before and after seven days of placement [6].…”
Section: Discussionmentioning
confidence: 99%
“…A dose of as few as 10 organisms freshly derived from humans or chickens may colonize young birds (3,4). The daily consumption of water by birds Ͼ30 days of age is approximately 250 ml (35), which is equivalent to 6,250 liters daily in sheds holding 25,000 birds (e.g., farm J). Given that older birds drink 250 ml of water daily, header tanks with a 1,000-liter capacity serving large flocks of older birds would be replenished continuously.…”
Section: Discussionmentioning
confidence: 99%